Pendidikan Pancasila sebagai Upaya Pencegahan Radikalisme di Kalangan Mahasiswa - Yuhasnil Yuhasnil; Pebriyenni Pebriyenni (JOEAI (Journal of Education and Instruction), 2026)
This study aims to analyze the role of Pancasila education in preventing radicalism among students at the Abdi Pendidikan Foundation Teacher Training College (STKIP). This study used a quantitative approach with a survey design. The results indicate that Pancasila education has a significant effect on reducing radical attitudes among students, with a significance value of 0.001 < 0.05. The higher the level of student understanding of Pancasila values, the lower the tendency towards radicalism. In conclusion, strengthening Pancasila education is an effective preventive strategy in countering radicalism in higher education.   Keywords: Students, Pancasila Education, Radicalism